2013
DOI: 10.1097/mph.0b013e3182830ffa
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance of Nontransplanted Childhood ALL Survivors is Comparable to Healthy Controls

Abstract: Physical fitness is an essential feature of overall health. Our objective was to compare the physical performance between nontransplanted acute lymphoblastic leukemia (ALL) patients (study patients), healthy controls, and ALL patients after stem cell transplantation (SCT). Forty-five ALL patients (median age, 13.3 y) treated without cranial irradiation were compared with 34 ALL patients (12.0 y) treated with SCT and total body irradiation and 522 age-matched and sex-matched controls. Their physical performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
4
25
0
3
Order By: Relevance
“…Jarvela et al 5 reported deficits in muscle performance and a 14% deficit in peak VO 2 when comparing 21 ALL survivors 16 to 30 years of age to age-and sex-matched controls, and Hartman et al 37 reported that mean performance on the 6-minute walk test was 2 SD below predicted, 5 years after therapy among 34 ALL survivors aged 9 to 18 years. In contrast, Taskinen et al 38 reported no differences in performance on 6 timed measures of physical fitness when comparing 45 ALL survivors aged 9 to 20 years to established reference values. 38 In our multivariable analysis among those not exposed to CRT, we found no specific chemotherapy agents or doses associated with proximal muscle weakness or exercise capacity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Jarvela et al 5 reported deficits in muscle performance and a 14% deficit in peak VO 2 when comparing 21 ALL survivors 16 to 30 years of age to age-and sex-matched controls, and Hartman et al 37 reported that mean performance on the 6-minute walk test was 2 SD below predicted, 5 years after therapy among 34 ALL survivors aged 9 to 18 years. In contrast, Taskinen et al 38 reported no differences in performance on 6 timed measures of physical fitness when comparing 45 ALL survivors aged 9 to 20 years to established reference values. 38 In our multivariable analysis among those not exposed to CRT, we found no specific chemotherapy agents or doses associated with proximal muscle weakness or exercise capacity.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Taskinen et al 38 reported no differences in performance on 6 timed measures of physical fitness when comparing 45 ALL survivors aged 9 to 20 years to established reference values. 38 In our multivariable analysis among those not exposed to CRT, we found no specific chemotherapy agents or doses associated with proximal muscle weakness or exercise capacity. This suggests that exposure to cellular toxic therapies may confer nonspecific general damage to underlying cellular structures that persists years after exposure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…19 Furthermore, results from these studies have been mixed, with one study 5 reporting no significant association between 6MWD and sports participation in childhood ALL survivors, and two studies reporting that more active childhood cancer survivors had better overall physical function, as measured with the 6MWT 6 and individual muscle performance tests. 19 Another study found that less physically active childhood cancer survivors felt more fatigued and had less physical strength and endurance. 18 The lack of observed association among PA, motor performance, and physical function in our study could be a result of several factors.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracycline treatment has well-documented, potentially long-term cardiotoxic side effects, and it potentially limits physical function. 16,17 Few studies have investigated whether motor performance or physical function impairments are related to PA levels in children who have completed treatment for ALL, 5,6,18,19 and to date, these studies have included childhood cancer survivors with a wide range in age and time since completing treatment. Given how important it is that children participate in PA for their normal growth and development, and recognizing that a suitable time to reintroduce habitual PA is once treatment for ALL is completed, 20 a better understanding of the factors associated with higher or lower PA levels in children shortly after completing treatment for ALL is needed.…”
mentioning
confidence: 99%